Making clinical academic careers more attractive: views from questionnaire surveys of senior UK doctors - Lambert, T; Smith, F; Goldacre, M (SAGE Publications, 2015)
Objectives To report on doctors’ reasons, as expressed to our research group, for choosing academic careers, and on factors that would make a career in clinical academic medicine more attractive to them. Design Postal, email and web questionnaires Participants 6936 UK-trained doctors who graduated in 1996, 1999 and 2000 Main Outcome Measures Open-ended comments about a career in clinical academic medicine. Results Of doctors who provided reasons for pursuing a long-term career in clinical academic medicine, the main reasons were enjoyment of academic work and personal satisfaction, whether expressed directly in those terms, or in terms of intellectual stimulation, enjoyment of research, teaching and the advancement of medicine, and the job being more varied than and preferable to clinical work alone. Doctors’ suggestions for making clinical academic medicine more attractive included improved pay and job security, better funding of research, greater availability of academic posts, more dedicated time for research (and less service work), and more support and mentoring. Women were more likely than men to prioritise flexible working hours and part-time posts. Conclusions Medical schools could provide more information, as part of student teaching, about the opportunities for and realities of a career in clinical academic medicine. Women, in particular, commented that they lacked the role models and information which would encourage them to consider seriously an academic career. Employers could increase academic opportunities by allowing more time for teaching, research and study; and should assess whether job plans make adequate allowance for academic work